2016
DOI: 10.1186/s13046-016-0304-4
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin (Lipitor) attenuates the effects of aspirin on pancreatic cancerogenesis and the chemotherapeutic efficacy of gemcitabine on pancreatic cancer by promoting M2 polarized tumor associated macrophages

Abstract: BackgroundInteractions of inflammatory cells with pancreatic cancer cells play crucial roles in pancreatic cancer, however the dynamic changes of inflammatory cell populations in pancreatic cancerogensis and after chemotherapy have not been well eclucidated. The combinational use of aspirin and atrovastatin (Lipitor) have been widely prescribled for cardio-cerebral vascular diseases mainly by regulation of inflammations, and they have been also reported to have plausible anti-tumor effects, however their poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 47 publications
(44 reference statements)
0
44
0
Order By: Relevance
“…Our results showed that the expression of CCL18 level in pancreatic cancer was significantly higher than that in corresponding normal pancreatic tissues (Supplementary Figure S1A ). It was recently reported that pancreatic TAMs are primarily polarized M2 macrophages that are associated with cancer progression and metastasis 10 , 11 . Hence, we utilized an experimental model of monocyte-derived macrophage polarization as described in the Supplementary Methods 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that the expression of CCL18 level in pancreatic cancer was significantly higher than that in corresponding normal pancreatic tissues (Supplementary Figure S1A ). It was recently reported that pancreatic TAMs are primarily polarized M2 macrophages that are associated with cancer progression and metastasis 10 , 11 . Hence, we utilized an experimental model of monocyte-derived macrophage polarization as described in the Supplementary Methods 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Although our findings agree with a previous meta-analysis that found no association between statin use and pancreatic cancer risk in healthy individuals, 6 they contrast with the substantial experimental evidence suggesting that statins inhibit pancreatic carcinogenesis. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] An explanation for this discrepancy may be that poor lifestyle choice such as excessive alcohol consumption, tobacco smoking or a high level of comorbidity, which is frequently seen in chronic pancreatitis patients, 40,41 may mitigate any potentially beneficial effect of statins. Furthermore, the potential anticancer effect of statins may differ according to statin solubility (i.e., lipophilic or hydrophilic), 42 which our study was not large enough to examine.…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, experimental studies suggest that statins can decrease pancreatic cancer risk by interfering with vital intracellular signaling pathways. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A recently published Danish case-cohort study of approximately 4,800 chronic pancreatitis patients suggested that statin use was associated with an 80% reduction in pancreatic cancer risk. 24 Although a compelling finding, the study reported a crude null finding and the beneficial effect of statins was only evident in a propensity-score matched analysis of 339 statin users (7% of the total population).…”
Section: Introductionmentioning
confidence: 99%
“…Although caution should be exercised for these findings, one potential explanation could be that a potential prognostic effect of statins is attenuated when used in combination with low-dose aspirin. 33,34 Alternatively, the different effect of post-diagnostic statin use by use of low-dose aspirin may reflect differences in population characteristics as the majority of users of low-dose aspirin have cardiovascular disease or risk. 35 On the other hand, statin use among non-users of low-dose aspirin is predominantly prescribed for indications other than cardiovascular prophylaxis, and mainly hyperlipidaemia.…”
Section: Discussionmentioning
confidence: 99%